Bridging the gap: translating and simplifying CFIR 2.0 for French practitioners in implementation science - Joanie Pellet; Sophie Pouzols; Valéry Ridde; Cédric Mabire (Implementation Science Communications)
Abstract Background The Consolidated Framework for Implementation Research (CFIR) 2.0 is widely used in implementation projects but can be difficult for non-researchers to apply due to its complexity. While a French version of the original CFIR exists, CFIR 2.0 had not yet been translated. This study aimed to translate and simplify CFIR 2.0 for healthcare practitioners in French-speaking Switzerland to improve its accessibility and utility. Method Using the Principles of Good Practice for Translation and Cultural Adaptation, the process included: (1) four independent forward translations, (2) reconciliation of simplified definitions, (3) online survey with 16 clinical nurse specialists to assess the content validity of the simplified definitions, (4) back translation, and (5) harmonization to finalize the French version. The content validity of each construct was assessed using the Content Validity Index (CVI), with further revisions based on feedback. Results Most participants found the simplified definitions understandable, with an average score of 1.46 (where 1 is "very easy to understand" and 2 is “easy to understand”). Thirteen items with lower I-CVI scores (≤ 0.78) were revised. The overall S-CVI was 0.87, indicating high content validity. Minor discrepancies in the back translation were resolved. Conclusions This study produced a French translation of CFIR 2.0 with simplified definitions tailored for healthcare practitioners. The high content validity and feedback underscore the need for contextually relevant adaptations to enhance the practical use of the CFIR framework. Further testing in diverse French-speaking contexts is necessary to refine the tool and broaden its applicability in real-world settings.